Avaliação da cobertura florestal da sub-bacia hidrográfica do rio Alegre, Sul do estado do Espírito Santo, utilizando geotecnologias - Silva, Kmila Gomes da (2012)
The analysis of the plant covering behavior on a temporal scale addresses practices that make forest remnant sustainability possible. The present study seeks to analyze the dynamics of the forest fragments in the hydrographic subbasin of the Alegre river, Espirito Santo state, based on the alterations of the plant covering and the structure of the forest landscape on a space-time scale, through two chapters. The first is based on the hypothesis that vegetation indexes can express similar vegetative or differentiated vigor of canopies of a specific area. To test the hypothesis, the objective was to to compare three vegetation indexes: TVI (Transformed Vegetation Index), CTVI (Corrected Transformed Vegetation Index) and RATIO (Ratio Vegetation Index), in relation to the behavior of NDVI (Normalized Difference Vegetation Index), regarding the discrimination of the vegetative vigor, as well as the alterations in the forest cover between 1987 and 2010. Through the obtained results, it was verified that the vegetation indexes allowed to estimate the vegetative vigor of the plant covering. A 4.90% (NDVI) increase and one of 7.78% (TVI) of forest covering, a pasture reduction of 3.34% (NDVI) and 5.53% (TVI) and a reduction of nonvegetated areas of 5.93% (NDVI) and 3.35% (TVI), in the period between 1987 and 2010 were evidenced. The natural regeneration process might have been the decisive factor for the area increrease and the changes in the forest vegetation of the area. The second chapter was based on the hypotheses that:1) In the forest landscape the predominance of fragments of small area occured during the years studied (1975, 2002 and 2007); 2) there is a predominance of forest fragments with complex forms and with smaller central area; 3) The forest remnants are isolated and with a larger border area. Based on the above, the aim was to characterize the space and temporal evolution of the forest fragment structures using landscape ecology metrics applied in the years of 1975, 2002 and 2007; the structural analysis of the forest fragments was conducted contemplating area parameters, form, nucleus, border and proximity by size classes. Based on the obtained results, a 7% increase was verified in the total area of the forest covering with the appearance of 645 new fragments. The number of fragments increased and the area of contribution small, which implied in the high border/area ratio. The smallest fragments (< 1 ha.) presented simple geometric form in relation to the others. The largest forest fragments (> 20 ha.) were shown proximate, presenting a tendency towards reduction of the proximity measure values